The Role of Textiles in Controlling Microclimate to Prevent Pressure Injury - Andriana Arfah; Saldy Yusuf; Yuliana Syam (Universitas Muhammadiyah Semarang, 2020)
Pressure injury (PI) is still a problem in health and home care both in developing and developed countries. PI is important to prevent because it has an impact on the physical, psychological, social, and economic aspects of the patient. One of the preventions of pressure injury is to choose the right textile, therefore this literature review aims to identify the right textile and can control microclimate in preventing PI. The Method used by searching the literature of scientific publications in the time of years between 2009-2019 using database Pubmed, Science Direct, Willey Online Library, Cochrane Library dan Google Scholar, there were 2.152 articles. The results of the literature review found six articles that fit the inclusion criteria and related to the use of textiles that can control microclimate in preventing pressure injury including textiles made from synthetic fabrics of silk, polyester, and synthetic fiber. Synthetic fiber textiles are best used as bedding because they control microclimate and reduce friction that can prevent the development of pressure injury.